Measuring regulatory focus - VanKrevelen, Steve (Kansas State University, 2017)
Regulatory focus has emerged as an important construct in the organizational sciences. In the past ten years more than 200 papers have been published applying regulatory focus to a wide variety of contexts ranging from marketing and persuasion to feedback and performance appraisal (Johnson et al., 2015). Despite the ubiquity of RFT’s application, only a few studies have targeted the psychometric properties of measures of regulatory focus; and the findings thus far suggest that improvement is needed. Haws (2010) evaluated five measures of regulatory focus and concluded that they differed substantially with respect to their theoretical content, and that most demonstrated unacceptably low internal consistency. Summerville & Roese (2008) drew similar conclusions in their evaluation of the Regulatory Focus Questionnaire (RFQ) and the General Regulatory Focus Measure (GRFM) and added that the two scales might actually be measuring different underlying constructs. Given the inconsistencies and problems associated with existing measures of regulatory focus, the purpose of the current research is to extend the critical evaluation of existing measures of regulatory focus and then to propose the development of a new measure based on rigorous scale development practices like those set forth in Hinkin, (1995) and Crocker & Algina, (1986). A new scale of Regulatory Focus was developed designed to measure all aspects of RFT and to test whether a two-factor or a four-factor SEM model fit the data best. The final scale consisted of 14 items. CFAs were used to test whether a two-factor or a four-factor model of regulatory focus fit the data best. Results suggested that both models fit the data equally well. However, for parsimony reasons and given that one of the latent factors of the four-factor model contained only two items (making any estimates of internal consistency difficult) the two factor model of regulatory focus was retained as the preferred model.
Keywords: Motivation; Regulatory focus; Self regulationMeasurement